The Effect Of Profitability And Liquidity Against Capital Structure (Case Study in Registered Property and Real Estate Sector Companies On the Indonesia Stock Exchange (IDX) Period 2014-2018) - Sev Rahmiyanti; Aziz Setyawan Nugroho (Primanomics : Jurnal Ekonomi & Bisnis, 2020)
This research was conducted to determine the effect of profitability and liquidity on capital structure. This study uses financial statement data on real estate and property companies listed on the IDX taken over a period of five years, starting in 2014 until 2018. These data were obtained from the site www.idx.co.id with the type of data used is a time series data. The results of this study indicate simultaneously the effect, profitability ratios and liquidity ratios, on real estate and property companies have a significant effect on capital structure with a large influence of only 21.5%. While partial liquidity has different effects in influencing capital structure. It can be concluded that the profitability ratio has a significant negative effect on the capital structure while the liquidity ratio has a significant positive effect on the capital structure.